Leasing in Vanuatu : Findings and Community Dissemination on Epi Island - Stefanova, Milena; Porter, Raewyn; Nixon, Rod (World Bank, Washington, DC, 2012)
Under the Vanuatu constitution, the 'rules of custom shall form the basis of ownership and use of land.' Implementing this principle after decades of land alienation, however, has proved to be challenging. While the leasing arrangement was originally intended to restore investor confidence and maintain agricultural development in newly independent Vanuatu, it soon evolved into the method of acquiring new leases over previously unalienated land. Tourism, business, agriculture, industry, urbanization, and the desire to use land to secure financial loans are some of the driving forces behind the creation of leases. This briefing note summarizes the findings of the research conducted on Epi Island and discusses methodologies for disseminating research findings to affected communities.